2019
DOI: 10.1136/neurintsurg-2018-014421
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of clinical presentation and angiographic findings in patients with indirect cavernous carotid fistulae

Abstract: IntroductionIndirect cavernous carotid fistulae (ICCFs) can present with insidious, non-specific symptoms and prove difficult to diagnose. This study evaluates associations among ICCF symptoms and angiographic findings.MethodsA retrospective analysis was performed of prospectively maintained records at four medical centers to identify patients with ICCFs evaluated with angiography. Patient demographics, symptoms, and angiographic findings were tabulated. Univariate and multivariate analyses were conducted to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…They postulated that penetration of the liquid agent into the matrix of the coil mass enables complete obliteration with less glue material (3). Alexander and colleagues found out that in their study cohort of patients with indirect CCF the complication rate was significantly lower when there was a combined use of Onyx and coils instead of Onyx as the sole embolic agent (26). We described a combination of those two materials in 25 cases of our study cohort (25/59, 42.4%).…”
Section: Discussionmentioning
confidence: 79%
“…They postulated that penetration of the liquid agent into the matrix of the coil mass enables complete obliteration with less glue material (3). Alexander and colleagues found out that in their study cohort of patients with indirect CCF the complication rate was significantly lower when there was a combined use of Onyx and coils instead of Onyx as the sole embolic agent (26). We described a combination of those two materials in 25 cases of our study cohort (25/59, 42.4%).…”
Section: Discussionmentioning
confidence: 79%
“…Arteriovenous fistulas are abnormal connections between arteries and veins. Dural arteriovenous fistulas (dAVFs) are typically between dural arteries and a venous sinus, most commonly at the transverse-sigmoid sinus, marginal sinus and/or condylar veins, cavernous sinus, or vertebral venous plexus . Dural arteriovenous fistulas are sometimes associated with venous sinus thrombosis, which may occur following an infection, trauma, or surgery.…”
Section: Discussion: Diagnosis By Categorymentioning
confidence: 99%
“…Alexander et al 7 found that the majority of patients with indirect CCF were females with mean age of 61 years, with mean duration from symptom onset to diagnosis of 234 days. Clinical signs and symptoms of CCF are conjunctival chemosis and injection, proptosis, ophthalmoplegia, pulsating exophthalmos, diplopia, orbital pain, bruits, increased IOP, and decreased vision.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial hemorrhage or hemorrhagic infarcts are rare but dangerous complications of CCF and are associated with cortical venous reflux (CVR). 7 , 9 , 10 Cortical venous reflux has been found to be more common in patients with diplopia, cranial nerve palsy, elevated IOP, chemosis, and bruit. 7 Traditional 4-vessel angiography (digital subtraction angiography) is the gold standard to diagnose CCF and CVR, which may show tortuous and engorged veins, delayed appearance of the veins and focal staining, along the region of CVR in the venous phase of vertebral or internal carotid arteriography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation